(untitled) (Japan, 2012)
Contents: Suitable stock management in tropical/subtropical areas, development of aquaculture technology suitable for Southeast Asia.
Keywords: Sustainable aquaculture,Nuôi trồng thủy sản bền vững; Southeast Asia,Đông Nam Á